Pola Sebaran Salinitas dengan Model Numerik Dua Dimensi di Muara Sungai Musi - Christie Indah Sari; Heron Surbakti; Fauziyah . (Maspari Journal : Marine Science Research, 2013)
The aim of this research is to describe the spread salinity with two dimensions numerical model at the Musi River’s estuary, and also to determined relationship of spread salinity with hydrodynamic unsure in water. The research has been done at Juli – Agustus 2011 at Musi River’s estuary, South Sumatra. Determination of sampling points is done by using purposive sampling method. The sample is measured by in-situ method and the data is proceed using Surface Water Modelling System (SMS 8.1) software, then verified with field measurement. The result of this research indicated that when the condition of sea-water tidal waters not too far into the river, the concentration of salinity in the surface layer (0.2 D) ranged between 6 - 28o/oo, in the water column (0.5 D) between 6 - 27o/oo, and in the deep waters (0.8 D) between 5 - 27o/oo. In other hand, at low tide condition, the influence of river moved farther out to the sea, with the concentration of salinity in the surface layer (0.2 D) ranged between 5 - 26o/oo, the salinity in the water column (0.5 D) and in the deep waters (0.8 D) between 4 - 27 o/oo. The result of spread salinity of the model simulation shows that the salinity distribution patterns follow the formed of the flow so that it can be said that the flow will affect the distribution of salinity in the waters. Based on the results of the flow simulation and salinity with or without the effects of wind’s flow and salinity patterns are the same, in the range 0.9 to 23.9o/oo. The verified average error result of measurement and simulation the model (MRE) with or without wind is 3,163 E-11%. So, factor of the wind did not significantly affect the movement of flow on the research.Keywords: Salinity distribution, Numerical models, SMS, Estuary